EVALUASI KECUKUPAN JUMLAH GURU SEKOLAH DASAR DI KABUPATEN SLEMAN TAHUN 2009 - Tukidi, - (Universitas Negeri Semarang, 2010)
This study aims (1) to obtain information about the conditions of the availability andadequacy of Elementary School (ES) teachers in Sleman Regency in terms of thenumber, academic qualification, and competence, and (2) to find out the distributionpatterns. This study was an evaluation study employing the document analysis. Theevaluation steps included: (1) setting the standard for the adequacy of the number ofteachers, (2) setting the index of the adequacy of teachers, and (3) analyzing theavailability and adequacy of teachers using the quantitative descriptive method. Theresults of the evaluation show that the availability of teachers is more than theminimum number, being excessive approximately 39%, and availability of teachers interms of academic qualification and competence meets only 43% and 14% of theminimum number of teachers. Besides, the information shows that the distribution ofthe number of teachers is not proportional to that of the number of students.Kata kunci: evaluasi, kecukupan, guruSD